2019
DOI: 10.1186/s13018-019-1317-4
|View full text |Cite
|
Sign up to set email alerts
|

Gout is not associated with the risk of fracture: a meta-analysis

Abstract: Background Numerous quantitatively based studies measuring the association between gout and the risk of fractures remain inconclusive. In order to determine whether gout could increase the risk of fractures, a meta-analysis was performed systematically. Methods Electronic databases, MEDLINE/PubMed, Embase, and Cochrane Library were systematically searched to identify studies evaluating the association of gout and the risk of fractures. No restrictions on language, publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…Although reported articles have demonstrated an increased prevalence of fractures especially in certain categories of gout patients [6] , the authors generally agree that the disease is not associated with an increased fracture risk, and that medical therapy aimed at reducing uric acid has no obvious benefit in preventing significant skeletal events [7] , [8] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Although reported articles have demonstrated an increased prevalence of fractures especially in certain categories of gout patients [6] , the authors generally agree that the disease is not associated with an increased fracture risk, and that medical therapy aimed at reducing uric acid has no obvious benefit in preventing significant skeletal events [7] , [8] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Gout has been associated with diabetes, obesity, hyperlipidemia, metabolic syndrome, insulin resistance, hypertension, renal disease, stroke, neurodegenerative diseases, and cardiac disease, and can lead to premature death [ 1 , 7 , 13 , 17 , 22 , 23 , 35 , 39 , 41 , 42 , 43 , 44 , 45 , 46 ]. Gout is not associated with an increased risk of fractures [ 47 ].…”
Section: Clinicalmentioning
confidence: 99%
“…Likewise, an extensive primary care medical data-based study in the United Kingdom reported no impact of gout on vertebral or non-vertebral fractures [ 19 ]. A meta-analysis concluded no definite identifiable risk for osteoporotic fractures at any site following gout in either males or females [ 20 ]. While most epidemiological studies have brought into focus the possible hazard for osteoporotic fractures following gout [ 11 , 16 , 17 , 18 , 19 , 20 ], data on incident osteoporosis that can increase fracture susceptibility are scarce [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis concluded no definite identifiable risk for osteoporotic fractures at any site following gout in either males or females [ 20 ]. While most epidemiological studies have brought into focus the possible hazard for osteoporotic fractures following gout [ 11 , 16 , 17 , 18 , 19 , 20 ], data on incident osteoporosis that can increase fracture susceptibility are scarce [ 21 , 22 ]. Fewer than ten studies have been published on gout and the subsequent development of osteoporosis [ 21 , 22 ] or fracture [ 11 , 16 , 17 , 18 , 19 , 20 ] since 2016, of which only two cohort studies dealt with osteoporosis risk [ 21 , 22 ], which has yet to be reproduced in combined analyses with both osteoporosis and vertebral and non-vertebral osteoporotic fractures in enough longstanding follow-up data.…”
Section: Introductionmentioning
confidence: 99%